Culeolus suhmi Herdman 1881 - Maggioni, Tamara; Rimondino, Clara; Taverna, Anabela; Reyna, Paola; Lagger, Cristian; Alurralde, Gastón; Calcagno, Emilia; Tatián, Marcos (Zenodo, 2022)
Culeolus suhmi Herdman, 1881 Figure 5 Culeolus suhmi Herdman 1881: 86; Sanamyan K. & Sanamyan N. 2002: 350, fig. 28, and synonymy; Sanamyan K. & Sanamyan N. 2005: 2015, fig. 8; Sanamyan K. & Sanamyan N. 2006: 331, fig. 13. Not Culeolus suhmi Millar, 1970: 136 (= Culeolus anonymus ). Material examined : 63°34’S, 50°41’W, station 13, 2610 m, 14 March 2005, five specimens. Description. All specimens have the same external appearance and size (Fig. 5A). On average, they measure 5.5 cm wide and 3.5 cm long. The tunic is dull brown, completely covered by small vesicles. The atrial aperture is completely surrounded by a circular crest of crowded papillae forming a wide band made up of two to three rows. The papillae forming the crest are also covered by vesicles, as the rest of the tunic (Fig. 5B). Three of the samples have an extension of the crest running along the whole mid-ventral side of the body. The remaining two samples have this extension interrupted a very short distance from the crest. There are approximately 25 wide oral tentacles with ramifications of first and second orders and of two different sizes. These are distributed interspaced in a circle. The oral velum has a smooth border. The pre-pharyngeal band is double and circular, with slight undulations. The dorsal tubercle has a “C” shape. The dorsal lamina consists of a series of triangular languets that extends from the base of the dorsal tubercle to almost the entrance of the esophagus. The mantle is thin and delicate, but the musculature is thick. Transversal and longitudinal muscle fibers form a gridded network that covers the totality of the body. The branchial sac has no stigmata. It consists of a mesh of longitudinal and transverse vessels. The branchial formula for the largest specimen is: E - 2 (8) 6 (10) 6 (12) 7 (15) 7 (12) 6 (11) 4 - DL DL - 4 (13) 5 (11) 6 (12) 10 (11) 8 (9) 4 (9) 4 - E The gut forms an open loop. The esophagus is short. The stomach is completely covered by hepatic diverticula. The border of the anus has multiple and small lobes. Except for one damaged specimen, there are two gonads on the left side and two gonads on the right side (Fig. 5C). The number of gonadal lobes varies between one and eight: the first specimen (3.5 cm long and 5.5 cm wide) has four lobes in the posterior left gonad, eight lobes in the anterior left gonad, three lobes in the posterior right gonad, and six lobes in the anterior right gonad; the second specimen (3.5 cm long and 7 cm wide) has five lobes in the posterior left gonad, seven lobes in the anterior left gonad, three lobes in the posterior right gonad, and seven lobes in the anterior right gonad; the third specimen (2.5 cm long and 5 cm wide) has four lobes in the posterior left gonad, five lobes in the anterior left gonad, three lobes in the posterior right gonad, and five lobes in the anterior right gonad; the fourth specimen (4 cm long and 6 cm wide) has four lobes in the posterior left gonad, five lobes in the anterior left gonad, three lobes in the posterior right gonad, and five lobes in the anterior right gonad; the fifth specimen (damaged; 1.8 cm long and 3 cm wide) has only one gonad on the left side inside the gut loop with six lobes, while both right gonads have one lobe each. The position of the gonads in relation to the gut-loop is constant in all the specimens. On the left side, both gonads have the same length as the descending limb of the gut-loop. On the right side, the gonads run parallel to the endostyle and to each other. The posterior gonad, closer to the endostyle, is shorter than the anterior (Fig. 5C). Adhered to the peduncle and to the ventral side of the body of two adult specimens, we found two solitary ascidians that could not be identified due to their early stage of development (Fig. 5A). They measure 1 cm wide by 1 cm long and 2 cm wide by 2 cm long and have an ovoid shape. The tunic that surrounds them is thin and transparent, with thin and numerous projections. Stomach contents. In the stomach of three specimens we found pellet-shaped material (fecal pellets). In addition, in one of these we also found a complete amphipod (undetermined). Remarks. This is the first record of Culeolus suhmi in the Southern Ocean. It is also the southern record and the only geographic location that is shared with C. anonymus . The genus Culeolus has a high intra-specific variability of characters frequently used for species identification (Monniot C. & Monniot F. 1976; Kott 2002; Sanamyan K. & Sanamyan N. 2002). These characters are the position and number of the gonads and the structure of the postero-ventral crest (Sanamyan K. & Sanamyan N. 2002). Monniot C. & Monniot F. (1976) used the position of the gonads in relation to each other and to the gut-loop and the border of the anus to establish differences between Culeolus suhmi and C. anonymus , a species cited for the SW Atlantic area. Based on new material and on revisions of previously identified material, Sanamyan K. & Sanamyan N. (2002) doubted the value of these characters for delimitation of the discussed species because they were highly variable. They concluded that the only character stable enough to distinguish between C. anonymus and Culeolus suhmi is the shape of the crest. The number of gonads is variable in some species of the genus Culeolus , like in Culeolus suhmi (Sanamyan K. & Sanamyan N. 2005). After the study of new material the authors concluded that, even though in the majority of specimens the number of gonads on the right side is two, it could also ascend to three. Previously, Sanamyan K. & Sanamyan N. (2002) had suggested that this could be the product of an abnormality. In regard to the ascidian epibionts found, we could only detect a rudimentary endostyle and digestive tract, with no signs of branchial sac, gonads or muscular tissue. Unfortunately, due to the condition of these specimens no more details could be provided. The presence of ascidians in an early state of development attached to the bodies of adult conspecific specimens has been associated with gregarious behaviours in shallow water environments (Manríquez & Castilla 2007; Castilla et al. 2007). In addition, some studies of associations among interspecific ascidians pointed to predation as the selective force maintaining the association (Young 1989; Davis 1996). Ascidian-ascidian associations, however, are not an exclusive attribute of shallow water environments. Although to a lesser extent, deep-sea ascidians have also been observed as basibionts and epibionts of other ascidians, including specimens of the genus Culeolus (Monniot C. & Monniot F. 1982; Sanamyan K. & Sanamyan N. 2002). Notwithstanding, the causes of this phenomenon at deeper depths still remain uncertain (Maggioni et al. in prep.). : Published as part of Maggioni, Tamara, Rimondino, Clara, Taverna, Anabela, Reyna, Paola, Lagger, Cristian, Alurralde, Gastón, Calcagno, Emilia & Tatián, Marcos, 2022, Abyssal ascidians (Chordata, Tunicata) from the Weddell Sea, Antarctica, including a new Styela species and stomach content identifications, pp. 296-314 in Zootaxa 5093 (3) on pages 303-304, DOI: 10.11646/zootaxa.5093.3.2, http://zenodo.org/record/5909824 : {"references": ["Herdman, W. A. (1881) Preliminary report on the Tunicata of the \" Challenger \" expedition. Part III. Cynthidae. Proceedings of the Royal society of Edinburgh, 11 (3), 52 - 58. https: // doi. org / 10.1017 / S 0370164600046782", "Millar, R. H. (1970) Ascidians, including specimens from the deep-sea, collected by the R. V. ' Vema' and now in the American Museum of Natural History. Zoological Journal of the Linnean Society, 49 (2), 99 - 159. https: // doi. org / 10.1111 / j. 1096 - 3642.1970. tb 00732. x", "Kott, P. (2002) Culeolus herdmani Sluiter, 1904 (Tunicata, Ascidiacea) from the northwestern Australian continental slope with an overview of the genus. Records of the Western Australian Museum, 21, 62 - 70. https: // doi. org / 10.18195 / issn. 0312 - 3162.21 (1). 2002.063 - 070", "Manriquez, P. H. & Castilla, J. C. (2007) Roles of larval behaviour and microhabitat traits in determining spatial aggregations in the ascidian Pyura chilensis. Marine Ecology Progress Series, 332, 155 - 165. https: // doi. org / 10.3354 / meps 332155", "Castilla, J. C., Manriquez, G. H., Delgado, A. P., Gargallo, L., Leiva, A. & Radic, D. (2007) Bio-foam enhances larval retention in a free-spawning marine tunicate. Proceedings of the National Academy of Sciences, 104 (46), 18120 - 18122. https: // doi. org / 10.1073 / pnas. 0708233104", "Young, C. M. (1989) Selection of predator-free settlement sites by larval ascidians. Ophelia, 30 (2), 131 - 140. https: // doi. org / 10.1080 / 00785326.1989.10430840", "Davis, A. R. (1996) Association among ascidians: facilitation of recruitment in Pyura spinifera. Marine Biology, 126, 35 - 41. https: // doi. org / 10.1007 / BF 00571375"]}